Transconstitutionalism or cosmopolitanism: perspectives for a dialogical semantics in the contemporary constitutionalism / Alexandre Douglas Zaidan de Carvalho - de Carvalho, Alexandre Douglas Zaidan (2014)
By considering the variety of elements that surrounds the fragmentation of law reproduction, beyond the precarious legitimacy of the national State and non-state entities to confront common constitutional problems of the world society, this paper discusses two theoretical proposals directed to the question: transconstitucionalism and constitutional cosmopolitanism. To draw a parallel between the two perspectives, it is intended to demonstrate the limits and possibilities of both, with special attention to the American constitutionalism. Focusing on the resistance of the Supreme Court to consider foreign precedents as reference to their decisions, the paper evaluates how the posture of closing the dialogue affects the construction of the notion of shared constitutionalism.